Deskripsi Profil Pasien Baru Vitiligo di Rumah Sakit Umum Daerah Tarakan Jakarta Periode Tahun 2023 - Irviani, Irviani; Hapsari, Saskia Retno Ayu (Jurnal MedScientiae, 2025)
Vitiligo caused by depigmentation process manifested as white macules and patches on body with prevalence about 0.5-2% of world populations and classified as non-segmental, segmental, and unclassifiable forms. The therapies include PUVA, NBUVB, topical corticosteroid, laser, and other topical therapies. Vitiligo patients of Tarakan Regional Hospital in 2022 were 9,199 and in 2023 were 10,385. This study was conducted to understand the description of new vitiligo patients profile at Tarakan Regional Hospital as comprehensive data to provide better therapy. The study design used descriptive retrospective study of new vitiligo patients at Tarakan Regional Hospital in 2023 with consecutive sampling from electronic medical record. New vitiligo patients at Tarakan Regional Hospital in 2023 were 105 patients. Majority was women total 58 patients (55.24%), largest age groups were 21-30 years old and 41-10 years old consist of 18 patients each group (17.14%), most frequent lesion is multiple in 98 patients (93.33%), most frequent location is face area of 67 patients (63.81%), most frequent type is vitiligo vulgaris in 87 patients (82.86%), and majority doesn’t have any comorbidities found in 92 patients (87.62%). The new vitiligo cases at Tarakan Regional Hospital in 2023 was 105, majority was women, multiple lesions, and vitiligo vulgaris.